2005
DOI: 10.1111/j.1365-2222.2005.02381.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical corticosteroid inhibits interleukin‐4, ‐5 and ‐13 in nasal secretions following allergen challenge

Abstract: Fluticasone propionate has selective inhibitory effects on Th2 cytokine synthesis following nasal challenge, while also decreasing release of chemokines, but not affecting levels of Th1 cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 42 publications
6
50
0
2
Order By: Relevance
“…Cytokines from T-helper (Th)-2 cells play an important role in orchestrating airway inflammation in asthma through the release of specific cytokines, and particularly on the infiltration of eosinophils, which is mediated by interleukin-5. The present author has shown that nasal grass pollen challenge gives a rapid increase in Th2 cytokines, including IL-5, measured by direct nasal sampling, and that this is completely inhibited by pre-treatment for 30 min with an inhaled corticosteroid [62]. This is likely to be due to an inhibitory effect of corticosteroids on the transcription factor GATA-3 in Th2 cells which regulates the synthesis of Th2 cytokines.…”
Section: Rapid Anti-inflammatory Effects In Clinical Studiesmentioning
confidence: 82%
“…Cytokines from T-helper (Th)-2 cells play an important role in orchestrating airway inflammation in asthma through the release of specific cytokines, and particularly on the infiltration of eosinophils, which is mediated by interleukin-5. The present author has shown that nasal grass pollen challenge gives a rapid increase in Th2 cytokines, including IL-5, measured by direct nasal sampling, and that this is completely inhibited by pre-treatment for 30 min with an inhaled corticosteroid [62]. This is likely to be due to an inhibitory effect of corticosteroids on the transcription factor GATA-3 in Th2 cells which regulates the synthesis of Th2 cytokines.…”
Section: Rapid Anti-inflammatory Effects In Clinical Studiesmentioning
confidence: 82%
“…This might partly be related to the applied doses of allergen and LPS, but also to the low number of patients examined. Along with several groups, we have shown that challenge with allergen, but not LPS, can cause local nasal symptoms [23] and that both allergen and LPS have the ability to release an array of cytokines in the nose [23,24,25,26,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that inhalative GC reduced Th2 cytokines in nasal fluids (IL-1a, IL-1b, IL-2, IL-3, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12, IL-13, IL-15, CCL-11, CCL-5, CCL-2 (MCP1), CCL-3, CXCL-10, GM-CSF, IFN-c and TNF-a) (169), but increased the relative frequency of Tregs that express the latent form of TGF-b1 (83,170). Also, systemic treatments with herbal drugs reduced nasal levels of IL-8 and leukotriene B4 (171).…”
Section: Biomarker Usage In Treatment Monitoringmentioning
confidence: 99%